Is prolonged immobilization a risk factor for symptomatic venous thromboembolism in elderly bedridden patients? - Gatt, Moshe E.; Paltiel, Ora; Bursztyn, Michael (Thrombosis and Haemostasis, 2004)
Prolonged immobilization and advanced age are considered to be important risk factors for venous thromboembolism (VTE). Nevertheless, the need for VTE prophylaxis in long-term bedridden patients is not known. To assess whether very prolonged immobilization (i.e. over three months) carries an increased risk for clinically apparent VTE, we performed a historical-cohort study of nursing home residents during a ten-year period. Data concerning patient’s mobility and incidence of overt deep vein thrombosis or pulmonary embolism were registered. The mean resident age was 85 ± 8.4 years. Eighteen mobile and eight immobile patients were diagnosed with clinically significant thromboembolic events, during 1137 and 573 patient-years of follow up, respectively. The incidence of venous thromboembolic events was similar in both chronically immobilized and mobile patient groups, 13.9 and 15.8 per thousand patient years, respectively (p = 0.77). The rate ratio for having a VTE event in the immobilized patient group as compared with the mobile group was 0.88 (95% Confidence Interval (CI) 0.33 to 2.13). When taking into account baseline characteristics, risk factors and death rates by various causes, no differences were found between the two groups. In conclusion, chronically immobile bedridden patients are no more prone to clinically overt venous thromboembolic events than institutionalized mobile patients. Until further studies are performed concerning the impact of very prolonged immobilization on the risk of VTE, there is no evidence to support primary prevention after the first three months of immobilization. Evidence for efficacy or cost effectiveness beyond this early period is not available.
Keywords: Venous thromboembolism; prolonged immobilization; bedridden; prevention; prophylaxis